Het gebruik van vaste verbindingen tijdens examens „tolken” - Zelenka, Eszter (FILOGI, 2021)
Collocations, interpreting, native-like, foreign language acquisition Third year BA students of Dutch at Károli University followed a one semester long interpreting course. During their oral exam they had an interpreting task from Hungarian to Dutch. In my research I wanted to answer two questions: firstly, to what extent do students use collocations while performing an interpreting task; secondly to what extent is their use of collocations native-like? Based on the recorded data we can see that students often realize that they should use a collocation but cannot always retrieve the right one. Grammatical constructions in the students’ native language, in our case Hungarian, play also a role in the choice of collocations.